ANALYSIS OF THE FORMATION OF STUDENTS ' READING COMPREHENSION SKILLS IN THE LESSONS OF THE NATIVE LANGUAGE AND READING LITERACY (World Bulletin of Social Sciences, 2023)
The article mainly describes the analysis of materials covering the reading comprehension processes of the native language and reading literacy textbooks in increasing reading literacy of Primary School students